American Clinical Neurophysiology Society's Standardized Critical Care EEG Terminology: 2021 Version. Issue 1 (January 2021) - Hirsch, Lawrence J.; Fong, Michael W.K.; Leitinger, Markus; LaRoche, Suzette M.; Beniczky, Sandor; Abend, Nicholas S.; Lee, Jong Woo; Wusthoff, Courtney J.; Hahn, Cecil D.; Westover, M. Brandon; Gerard, Elizabeth E.; Herman, Susan T.; et al.
Abstract : Supplemental Digital Content is Available in the Text.